The application of checklists in environmental studies in the field of road construction - Gałaś, Slávka; Bohatkiewicz, Janusz (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
Checklists are one of the simplest but very effective methods used in the phase of planning, preparation and verification of activities, among others in the process of environmental impact assessment. These checklists can be used as a useful tool in every phase of the evaluation process to check the quality of the data used and the work performed and to verify the completeness of the assessments. The aim of the article is to show the applicability of checklists in environmental studies in the field of road construction on the domestic examples and from abroad.